Financial Literacy around the World : An Overview of the Evidence with Practical Suggestions for the Way Forward - Xu, Lisa; Zia, Bilal (World Bank, Washington, DC, 2012)
Financial literacy programs are fast becoming a key ingredient in financial policy reform worldwide. Yet, what is financial literacy exactly and what do we know of its effectiveness? This paper collects insights from the literature thus far and summarizes global evidence on financial literacy, its correlates, and existing and upcoming causal investigations. The authors conclude with a synthesis of policy advice and practical suggestions for the way forward in this fast growing area of research.